2022
DOI: 10.1038/s41419-022-05137-5
|View full text |Cite
|
Sign up to set email alerts
|

ACSL4-dependent ferroptosis does not represent a tumor-suppressive mechanism but ACSL4 rather promotes liver cancer progression

Abstract: Ferroptosis is a novel type of programmed cell death that differs from apoptosis in that it involves iron-dependent peroxidation of membrane phospholipids. Its role in a variety of human disorders, including cancer has been hypothesized in recent years. While it may function as an endogenous tumor suppressor in a variety of cancers, its role during initiation and progression of liver cancer, particularly hepatocellular carcinoma (HCC), is yet unknown. Because HCC is most commonly found in chronically injured l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…However, the association between ACSL4-induced tissue damage and HCC is likely to more nuanced because in a diethylnitrosamine carbon tetrachloride, chemically induced liver injury disease model, there was increased hepatic fibrosis when ACSL4 was expressed, and under such circumstances, there was also a subsequent increase in tumour progression which manifested as larger tumours. 127 These results are noteworthy since they demonstrate that at least in these experimental models, ACSL4-dependent ferroptosis during liver injury neither initiates nor suppresses the formation of HCC but may increase tumour progression in instances where ACSL4-dependent cell death leads to fibrosis. Furthermore, the authors also considered that the effects of ACSL4 on tumour growth might be mediated through functions other than ferroptosis such as upregulated lipid metabolism, which would align with other recent work in this area.…”
Section: Ac S L4 Involvement In Nafld and Na S Hmentioning
confidence: 81%
See 2 more Smart Citations
“…However, the association between ACSL4-induced tissue damage and HCC is likely to more nuanced because in a diethylnitrosamine carbon tetrachloride, chemically induced liver injury disease model, there was increased hepatic fibrosis when ACSL4 was expressed, and under such circumstances, there was also a subsequent increase in tumour progression which manifested as larger tumours. 127 These results are noteworthy since they demonstrate that at least in these experimental models, ACSL4-dependent ferroptosis during liver injury neither initiates nor suppresses the formation of HCC but may increase tumour progression in instances where ACSL4-dependent cell death leads to fibrosis. Furthermore, the authors also considered that the effects of ACSL4 on tumour growth might be mediated through functions other than ferroptosis such as upregulated lipid metabolism, which would align with other recent work in this area.…”
Section: Ac S L4 Involvement In Nafld and Na S Hmentioning
confidence: 81%
“…In adrenocortical tumour cells, ACSL4 can undergo hormone-induced phosphorylation 123 and there is now a precedent for ACSL4 activation by phosphorylation catalysed by PKCβII during ferroptosis 61 -a process likely to be relevant for precancerous liver disease. 127 Another recently described post-translational modification of ACSL4 with potential relevance to hepatocarcinogenesis is its O-GlcNAcylation catalysed by N-acetylglucosaminyltransferase, and this is associated with ACSL4-upregulated mTOR signalling. 37 Elevated protein O-GlcNAcylation is associated with increased oncogenesis in HCC and is thought to result from aberrant glucose metabolism (eg, see [158][159][160][161] ).…”
Section: P Os T-tr Ans L Ational Reg Ul Ation Of Ac S L4 E Xpre Ss I ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The question is whether other available fatty acyl CoA enzymes are involved in the formation of PUFA-CoA in NAT10 KD cells. Recently, it was reported that ACSL4 promotes cancer progression and therefore ACSL4-dependent ferroptosis does not necessarily represent tumor suppression (38). Another study challenges the current view of ACSL4 as the universal ferroptosis regulator for the following reasons ferroptosis is mostly induced in GPX4-dependent inhibition using RSL3, however, SLC7A11 inhibition with erastin or cystine starvation induces ferroptosis either from GPX4-dependent or GPX4-independent mechanisms, this is because the cystine uptake is not only important for glutathione synthesis but also biomolecules such as coenzyme A (CoA) (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent study found that an ACSL4-dependent process plays an unexpected cancer-promoting role in HCC formation. In an HCC model of chronic liver injury, loss of 5 Oxidative Medicine and Cellular Longevity ACSL4 significantly impaired the progression of tumor growth, accompanied by lower levels of tissue fibrosis and proliferation [53]. ACSL4-dependent ferroptosis establishes a link between tissue fibrosis and tumor progression, and hepatocyte ferroptosis is a breakthrough target that aggravates fibrotic and proliferative events as a promoter of HCC growth.…”
Section: Ferroptosis and Livermentioning
confidence: 99%